Autonomy in the reproductive health of quilombolas women and associated factors - Elionara Teixeira Boa Sorte Fernandes; Sílvia Lúcia Ferreira; Cláudia Suely Barreto Ferreira; Eliene Almeida Santos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Identify the level of reproductive autonomy of quilombola women and associate it with sociodemographic characteristics and aspects of sexual and reproductive health. Methods: Cross-sectional census study carried out in quilombola communities in a municipality in Bahia. Data was collected through questionnaires from the National Health Survey and the Reproductive Autonomy Scale, applied to quilombola women who agreed to participate. Descriptive statistics procedures were used and associations were made between reproductive autonomy scores and sociodemographic and reproductive characteristics. Results: The average total score for reproductive autonomy was 2.06. An association was found between the "decision-making" score and marital status. The score for "total reproductive autonomy" was associated with the use of contraceptive method. Conclusion: The reality of the study participants converges with the literature regarding the interference of sociodemographic and reproductive factors in the reproductive autonomy of black women.